Thrombin dynamics and clinical events in cirrhosis: low prothrombin conversion predicts bleeding risk - Ruth Anne Laura Willems; Alberto Zanetto; Elena Campello; Joke Konings; Cristiana Bulato; Matthijs Kramer; Francesco Paolo Russo; Mark Roest; Marco Senzolo; Patrizia Burra; Hugo ten Cate; Judith de Vos-Geelen; et al. (Frontiers in Cell and Developmental Biology, 2026)
Pro- and anti-coagulant factors are significantly altered in liver cirrhosis resulting in an increased bleeding and thrombosis risk. The thrombin generation (TG) test often seems unaltered in cirrhosis, indicating that a new hemostatic balance is reached. TG is determined by prothrombin conversion and thrombin inactivation. These processes can be quantified using the computational thrombin dynamics (TD) add-on analysis for the TG test. We studied TD parameters in cirrhosis to explore its predictive potential for bleeding and thrombosis. In the current study, 32 CP-A, 22 CP-B and 41 CP-C cirrhosis patients and 20 healthy controls were enrolled. Cirrhosis was predominantly alcohol-related (52%), while viral and metabolic etiologies accounted for 34% and 14% of cases, respectively. Patients receiving anticoagulant therapy were excluded. TG was measured using PPP Reagent Low in the presence and absence of thrombomodulin. TG peak height and velocity index were higher in patients than controls (+20%,p = 0.039 and +70%,p = 0.002), and time-to-peak was shorter (−18%,p < 0.0001). TD parameters were obtained computationally based on TG and coagulation factor data. The amount of prothrombin converted (PC tot ) was significantly reduced in patients (−43%,p < 0.0001), and the magnitude of the reduction was associated with disease severity. The maximum rate of prothrombin conversion (PC max ) showed a trend towards higher levels in CP-A patients. On the anticoagulant slide, the thrombin decay capacity (TDC) was significantly lower in patients (−44%,p < 0.0001), indicating a newly developed balance between pro- and anticoagulant processes that result in a slightly procoagulant TG phenotype. Four patients experienced bleeding and seven experienced thrombosis during follow-up (median = 499 days; CI: 478–524 days). Low maximum prothrombin conversion rates (PC max ) were associated with an increased hazard of bleeding. Patients in the lowest 20% of PC max had a HR of 12.9 (95% CI 1.34–124.31, p = 0.027) for bleeding. Low thrombin-α 2 Macroglobulin (T-α 2 M) complex formation was significantly associated with thrombosis during follow-up. Patients in the lowest quintile of T-α 2 M had a HR of 6.6 (95% CI 1.47–29.9, p = 0.014) for thrombosis. We conclude that reduced prothrombin conversion and thrombin inactivation result in rebalanced TG in cirrhosis patients. Our results demonstrate the potential clinical usefulness of TD parameters for the stratification of bleeding and thrombotic risk in cirrhosis patients.